2012
DOI: 10.1159/000339598
|View full text |Cite
|
Sign up to set email alerts
|

Dry Eye Symptoms in Patients after Eyelid Reconstruction with Full-Thickness Eyelid Defects: Using the Tomey TG-1000 Thermographer

Abstract: Background: Large full-thickness eyelid defects are conventionally reconstructed by either a Hughes flap or Cutler-Beard bridge flap. Since the structure of the eyelid and its components are necessary for the tear film production and stability, we investigated the outcome after eyelid reconstruction focusing on dry eye symptoms using a new thermographic device, the TG-1000. Methods: Seventeen eyes of patients formerly treated with Hughes flaps (n = 16) and a Cutler-Beard bridge flap (n = 1) were compared to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
2
10
2
Order By: Relevance
“…Thermography does not have the benefit of knowing the signal source, because it is [180] 2013 2a 1 ---Arita et al [181] 2013 2a 1 ---Purslow [182] 2013 1a 1 ---Klamann et al [183] 2013 2a 1 ---Petznick et al [184] 2013 2a 1 ---Gonnermann et al [178] 2012 2a 1 ---Kottaiyan et al [185] 2012 2a 1 ---Tan et al [186] 2011 4a 1 ---Kamao et al [187] 2011 2a 2 -83 80 Tan et al [188] 2010 4a 1 ---Tan et al [189] 2010 3a 1 ---Tan et al [190] 2010 2a 1 ---Acharya et al [191] 2009 4a 1 ---Chiang et al [192] 2006 2a 2 -79.3 75 Purslow et al [193] 2005 2a 2 ---Cherkas et al [194] 2003 2a 1 ---Morgan et al [195] 1999 1a ----Mori et al [196] 1997 1a 1 ---Morgan et al [197] 1996 2a 1 ---Morgan et al [198] 1995 2a 1 --- Table 6: Pain and inflammation diagnosis results. Authors Year MP PE A (%) Se (%) Sp (%) Jeong et al [203] 2013 2b ----Dibai Filho et al [204] 2013 1b 1 ---Kang et al [202] 2013 2b ----Rodrigues-Bigaton et al [88] 2013 1a 2 -62.2 75.6 Dibai Filho et al [205] 2013 1a 2 60 55.8 55.8 Zaproudina et al [206] 2013 2a 1 ---Roy et al [207] 2013 2a 1 ---Choi et al [201] 2013 2b 1 ---Zaproudina et al [208] 2013 2a 1 ---Frize and Ogungbemile [209] 2012 3b 3 -96 92 Hildebrandt et al [210] 2012 2b ----Laino [211] 2012 2b ----Wu et al [212] 2009 2b 1 ---Chang et al [213] 2008 1b 1 ---Niehof et al [214] 2007 2a 2 -74.3 83.9 Park et al …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermography does not have the benefit of knowing the signal source, because it is [180] 2013 2a 1 ---Arita et al [181] 2013 2a 1 ---Purslow [182] 2013 1a 1 ---Klamann et al [183] 2013 2a 1 ---Petznick et al [184] 2013 2a 1 ---Gonnermann et al [178] 2012 2a 1 ---Kottaiyan et al [185] 2012 2a 1 ---Tan et al [186] 2011 4a 1 ---Kamao et al [187] 2011 2a 2 -83 80 Tan et al [188] 2010 4a 1 ---Tan et al [189] 2010 3a 1 ---Tan et al [190] 2010 2a 1 ---Acharya et al [191] 2009 4a 1 ---Chiang et al [192] 2006 2a 2 -79.3 75 Purslow et al [193] 2005 2a 2 ---Cherkas et al [194] 2003 2a 1 ---Morgan et al [195] 1999 1a ----Mori et al [196] 1997 1a 1 ---Morgan et al [197] 1996 2a 1 ---Morgan et al [198] 1995 2a 1 --- Table 6: Pain and inflammation diagnosis results. Authors Year MP PE A (%) Se (%) Sp (%) Jeong et al [203] 2013 2b ----Dibai Filho et al [204] 2013 1b 1 ---Kang et al [202] 2013 2b ----Rodrigues-Bigaton et al [88] 2013 1a 2 -62.2 75.6 Dibai Filho et al [205] 2013 1a 2 60 55.8 55.8 Zaproudina et al [206] 2013 2a 1 ---Roy et al [207] 2013 2a 1 ---Choi et al [201] 2013 2b 1 ---Zaproudina et al [208] 2013 2a 1 ---Frize and Ogungbemile [209] 2012 3b 3 -96 92 Hildebrandt et al [210] 2012 2b ----Laino [211] 2012 2b ----Wu et al [212] 2009 2b 1 ---Chang et al [213] 2008 1b 1 ---Niehof et al [214] 2007 2a 2 -74.3 83.9 Park et al …”
Section: Discussionmentioning
confidence: 99%
“…These temperature changes can be linked to eye diseases, such as dry eye and dry eye after eye lid reconstruction [178]. Therefore, this technique is beginning to play an important role in the field of ophthalmology [179].…”
Section: Eyementioning
confidence: 99%
“…We have demonstrated that the temperature of a functional bleb is lower than that of a non-functional bleb [11], and the temperature of the corneal surface in eyes with the dry eye syndrome is lower than that in normal eyes [13]. It has also been reported that thermography is useful in evaluating bacterial corneal ulcers or the effect of reconstruction of lagophthalmos [26,27]. …”
Section: Discussionmentioning
confidence: 99%
“…The modified Hughes tarsoconjunctival flap is widely used for posterior lamella repair during full‐thickness lower eyelid reconstruction, following tumour excision or trauma . The flap bisects the meibomian glands in the upper tarsal plate and places the donor flap into the lower eyelid defect . However, the effects of this procedure on tear film function have not yet been fully established …”
Section: Measurements Of Operated Eyes With Modified Hughes Tarsoconjmentioning
confidence: 99%